THE CHARACTER-BASED MODULES AND THEIR INFLUENCE ON HISTORICAL AWARENESS OF STUDENTS OF CLASS XI MIPA 4 SMAN PASIRIAN - Irma Kristanti; Sumardi Sumardi; Nurul Umamah (JURNAL HISTORICA, 2019)
The development of history learning module that can improve historical awareness is the demand of 2013 curriculum at this time.Educators are expected to have the ability to develop teaching materials according to the students’ need in order to help teaching and learning activities and to improve the quality of learning. This research aims to produce character-based historical learning modules that may develop the students’ historical awareness.The subjects of this research were 2nd grade of MIPA 3 and MIPA 4 of Pasirian Senior High school included of 44 students.This research was conducted in February to March, 2019. The results showed that the character-based historical learning modules were validated with very good categories; the expert validation of field content was 88%, the expert validation of learning design was 92%, the expert validation of linguist was 96%, the user test was 98%.By using the product which has been valid was seen the improvement of historical awareness. The percentage on small group trials before learning was 51,75% and after learning was 87,75%, so it was got improvement in the amount of 86,75%. The percentage on large group trials before learning was 61% and after learning was 87,5%, so it was got improvement in the amount of 86,5%. The improvement of historical awareness on groups trials includes in very high category.The Conclusion of this research is a validated character-based history learning module and able to increase students' historical awareness. Keywords: The Character-Based Historical Learning Modules, Historical Awareness